Neonatal treatment with fluoxetine reduces depressive behavior induced by forced swim in adult rats - Mendes-da-Silva, Cristiano; De Souza, Sandra Lopes; Barreto-Medeiros, Jairza Maria; De Freitas-Silva, Sebastião Rogério; Costa Antunes, Daniela Eugênia; Urbano Cunha, Allan Delano; Ribeiro Ribas, Valdenilson; Simões de França, Maria Flávia; Nogueira, Maria Inês [UNESP]; Manhães-de-Castro, Raul (FapUNIFESP (SciELO), 2002)
Serotonin plays a role at the pathophysiology of depression in humans and in experimental models. The present study investigated the depressive behavior and the weigh evolution in adult rats (60 days) treated from the 1st to the 21st postnatal day with fluoxetine, a selective serotonin reuptake inhibitor (10 mg/kg, sc, daily). The depressive behavior was induced by the forced swim test (FST). The animals were submitted to two sessions of FST: 1st session for 15 min and the 2nd session 24h later, for 5 min. During the 2nd session the Latency of the Attempt of Escape (LAE) and Behavioral Immobility (BI) were appraised. The Fluoxetine group when compared to the Control group, showed an increase in LAE and a decrease in BI. The neonatal administration of fluoxetine reduced the depressive behavior in adult rats, possibly by increase in the brain serotonergic activity. This alteration can be associated to process of neuroadaptation.
Keywords: Depression; Neurogenesis; Selective serotonin reuptake inhibitor; Serotonin